PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ADOBE FLASH PADA MATA PELAJARAN KELISTRIKAN KENDARAAN RINGAN (TKR) DI SMK NEGERI 1 PALOH: Pengembangan Media Pembelajaran Interaktif Berbasis Adobe Flash Pada Mata Pelajaran Kelistrikan Kendaraan Ringan (TKR) di SMK Negeri - CHERY CHERY (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2023)
The purpose of this research is to produce a cooling system learning media that is easy to operate and suitable for use in learning activities. This research uses Research and Development research with 10 steps of media development. The technique used in data collection is using a validation sheet. The data analysis technique used quantitative analysis. The results of the validation data on media experts showed that the learning media for the cooling system based on Adobe Flash was in accordance with the average percentage of 90% which included three aspects of the assessment, including aspects of the display on the media, the use of images, sound and evaluation questions, and the navigation system. The results of the material expert validation show that Adobe Flash-based technical drawing learning media is very feasible to use with an average of 86.5% which includes three aspects of assessment, namely: aspects of material relevance, aspects of learning material content, and aspects of ease of operation.